GE_GERICHTE P/23210/2022 vom 27. November 2024 - GE Cour de justice (2024)
ORDONNANCE PÉNALE;OPPOSITION(PROCÉDURE);RESTITUTION DU DÉLAI;EMPÊCHEMENT NON FAUTIF;CERTIFICAT MÉDICAL;DÉFAUT(CONTUMACE) | CPP.356.al4; CPP.94